PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN DENGAN CORPORATE SOCIAL RESPONBILITY SEBAGAI VARIABEL INTERVENING - Risma Musfiyana; Nurul Inayah (Sekolah Tinggi Ilmu Ekonomi Semarang, 2022)
Firm value is the investor's perception of the company success which is often associated with stock prices. The purpose of this study is to analyze the effect of GCG on firm value with CSR as the Intervening variable. The population in this study are manufacturing companies in the basic and chemical industry sectors listed on the IDX. The sample was selected using purposive sampling method and find 38 companies that have met the sample criteria. The research data were analyzed using multiple regression methods and path analysis. The results of this study found that Independent Commisioners and Commite Audit does not have any effect on CSR disclosure. CSR have a significant effect on firm value, while Independent Commisioners and Commite Audit has no effect on the firm value. Then CSR is not able to mediate the relationship between GCG on firm value.